Poética da interpretação musical: a clarineta e o clarinetista - Moreno, Hugo Macêdo Serrão (2018)
The purpose of this paper is to discuss aspects of artistic research recommended by Marcel Cobussen (COBUSSEN, 2007) relevant to musical artistic creation and clarinet performance, especially the relation between clarinet and clarinetist. It is intended to discuss this relation beyond the traditional modern framing of the subject/object relationship, inserted in a poetic context. We consider it is important to launch a critical view on the artistic knowledge produced inside universities, and to reflect about questions of truth from the poetic dimension. To this end, we use Heidegger’s ontological statute as an overcoming exclusivity of world relations and its consequences in relation to the limits imposed by science in the production of knowledge. This limitation is consolidated through the dissociation between earthman and the world; body and soul; intelligibility and sensitivity in relation to an artistic approach. More than a scientific limit, such dissociation ratifies the intramundane and teleological sense of the Western man from the perspective of the Cartesian modern conception. Starting from an artistic perspective, poetic – creative –, we investigated the the happening of the clarinetist performance. However, we will not think about that relation as an isolated and closed event. Furthermore, we will not use concepts of musical criticism or aesthetics. In a poetic approach, Art claims an immediate and singular manifestation, not by parts or representations. These representations relate to the Work through rational mediation, as in the theory of knowledge. Our investigation proceeded from relations of interpretation since the immediatism of the senses (FOGEL, 2007). This conjunction of relationships is arranged in a sense beyond or below Cartesian objectivity. The intention of poetic production is the unveiling of the work – Aletheia. Therefore, we produced two recitals with pieces by Brazilian composers in which the clarinetist’s performance displays a sensitive and cohesive manifestation working in its own sense, which is performance as a factor intrinsic to the work of art. In this regard, the truth of a work is the process of manifestation of its own sense. After all, a work only exists with its performance, which is a part of the work. The unveiling of a work, according to (HEIDEGGER, 2010), manifests in the gap of work, art and artist. This gap as well as the relations established in the course of this research turns in results impregnated in the interpretation itself. About the Tripartite’s relationship in the work of art, according Heidegger, we perceive that the artist experiences a series of relations still not much discussed, because in general there is favoring of a technical and analytical understanding of the performance and little is spoken of the artistic experience.